1997
DOI: 10.1109/70.611319
|View full text |Cite
|
Sign up to set email alerts
|

Robotic stiffness control and calibration as applied to human grasping tasks

Abstract: In this paper, we study stiffness analysis as applied to human grasping. Grasp stiffness has been demonstrated to be useful for modeling and controlling robotic manipulators.The computation of general linear < 323 stiffness matrices for grasping, which can be decomposed into symmetric (conservative) and antisymmetric (nonconservative) components, offers physical insights for stiffness control in robotics as well as human grasping. Methods of stiffness calibration, using least-squares best fits with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 21 publications
(53 reference statements)
3
41
0
Order By: Relevance
“…This has been shown recently, in relation to the stiffness of the thumb and index finger during a grasping task [7]. Studies of the impedance of the human arm indicate that directional differences in stiffness can be as large as an order of magnitude [8].…”
mentioning
confidence: 99%
“…This has been shown recently, in relation to the stiffness of the thumb and index finger during a grasping task [7]. Studies of the impedance of the human arm indicate that directional differences in stiffness can be as large as an order of magnitude [8].…”
mentioning
confidence: 99%
“…Their analysis showed that unmatched finger stiffness and applied contact forces may destabilize the grip. Interestingly, some stiffness models in robotic grasping appear to effectively model human grasping behavior as well [12].…”
Section: B Grasp Stiffness and Interaction Controlmentioning
confidence: 99%
“…Shimoga [24] summarized the conventional grasp synthesis algorithms for robot hands. Also, Kao et al [25] tried to apply stiffness models usually employed in robotics research to the analysis of human grasping behaviors. In addition, grasp planning and control algorithms for multifingered robot hands have been proposed [49]- [51].…”
Section: Introductionmentioning
confidence: 99%